Studi Fase Terjadinya Rework pada Pekerjaan Konstruksi Gedung di Kabupaten Bireuen - Yanis, Muhammad (JURNAL VARIASI, 2011)
Rework is one of main contributors of cost increasing and project delay and resulting in bad performance and productivity. By considering of the big enough of bad impact of project performance that con be caused by it, the efforts to decrease the rework in construction stages is needed extremely. The objective of the study is to know the phase of rework in building construction project of Bireuen Regency. The data was gotten by giving the ranking questionnaire to 3owners sample, 15 supervision consultants sample, and 20 contractors sample, byclustering phase of rework into design phase, construction phase and both of thephase. Data preparation and analysis were conducted after reliability test byusing 5P55 v.13. The result showed that design phose beccime the major phose of rework,followed by construction phase and both of construction and design phase